STRATEGIZING SMALL AND MEDIUM ENTERPRISES DEVELOPMENT THROUGH ICT-RELATED INNOVATIONS ADOPTION: MODERATING INFLUENCE OF GENDER, AGE AND EXPERIENCE - Ibrahim, Adamkolo Mohammed (Informasi, 2018)
The rapid advancement in information and communication technology (ICT) has brought huge entrepreneur benefits and challenges. A key challenge that has been less researched is the demand for skilled manpower in relation to the issue of the role employees’ age and gender play in driving SMEs’ ICT-related innovations adoption. This paper attempted to determine the moderating role of three important workers’ demographic characteristics (age, gender and experience) on the use of innovations related to ICT by SMEs. Adopting the unified theory of acceptance and use of technology (UTAUT) perspective, a questionnaire was designed and administered to 400 employees selected from 43 SMEs in the Malaysian state of Selangor. The results of multiple regression analysis indicate that performance expectancy, effort expectancy, social influence and facilitating conditions all have significant impacts on ICT-related technology innovations adoption (ICTRIA) while the moderator analysis confirmed that the two gender categories, different age groups and different experience levels have specific moderating influence on the relationship paths between the four predictors and technology innovations use. Novel findings show that performance expectancy and social influence are more salient for older female and younger female workers to run jobs related to ICT innovations use in the firm respectively.